Parenting Stress and Styles as Predictors of Verbal Aggression in Early Childhood: A Study in Pemalang Kindergartens - Uni Haryanti, Dwi; Liftiah, Liftiah; Diana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Verbal aggression in early childhood, often characterised by behaviours such as mocking, cursing, and insulting, is a growing concern influenced by parenting stress and parenting styles. This study aims to analyse the relationship between parenting stress and parenting styles and their effects on verbal aggression in young children. A quantitative descriptive approach was employed, involving 125 parents from seven kindergartens in Pemalang Regency. Data collection utilised validated questionnaires, and the sample was determined through proportional sampling. The analysis included descriptive statistics, partial significance testing (T-test), and linear regression. The findings reveal that parenting stress has a significant effect on verbal aggression, with a significance value of 0.002 (< 0.050). Parenting style was also shown to significantly influence verbal aggression, with a significance value of 0.000 (< 0.050). Collectively, these variables were found to substantially contribute to the level of verbal aggression in early childhood. This research underscores the importance of addressing parenting stress and promoting positive parenting styles to mitigate verbal aggression in young children. Limitations include focusing solely on parenting variables and the absence of longitudinal analysis. Future research should explore additional contributing factors, such as socioeconomic status and child temperament, to develop comprehensive intervention strategies.